Velhice feminina: um debate feminista - Gomes, Paula Karina Soares (Brasil, 2023)
Female old age is a fact and a worldwide trend. Worldwide, there is a higher percentage of women, present in the fact that women have a longer life expectancy than men, evidencing the so-called feminization of old age. However, even though i livemore than men and old age has the predominantly female face, old age presents itself in a very particular way for women, because they are surrounded by prejudices, discrimination, exclusion and invisibility, leading them to live in conditions of social vulnerabilities considering social class which are inserted. The objective of this work is to draw an overview about female old age in the Brazilian context. To achieve this goal, we first sought to situate the demographic data surrounding old age and aging in Brazil and Amazonas, later the age prejudices against the elderly person in capitalist society sharpened in the covid-19 pandemic and finally conceptualize the feminization of old age. For this, we have selected the method of investigation of dialectical historical materialism that allowed us to understand the object in its entirety. The methodological procedures adopted were qualitative, bibliographic and documentary research. The discussion in this work leads us to the understanding that old age in Brazil is a stigmatized and devalued category that should be avoided and Brazilian older women, most of whom live in situations of social vulnerability. It was also verified the great influence on gender issues regarding the roles, social, cultural and economic values and standards that strongly reflect on female old age and the omission of feminist movements on the issues of old age and the elderly woman of their theoretical analyses.